The pet store pet show - Gallagher, Diana G; Puglisi, Adriana (North Mankato, Minnesota Capstone, 2014)
Mr. J's Pet Haven is losing business to a pet superstore, so he decides to put on a pet show for the neighborhood, and recruits Kyle and Mia to help
English stories
GRL: M
006-008
1 2 13 15
NEW_ZTN_GN
Keywords: Contests -- Juvenile fiction; Pet shows -- Juvenile fiction; Pets -- Juvenile fiction; Small business -- Juvenile fiction; Contests -- Fiction; Pet shops -- Fiction; Pet shows -- Fiction; Pets -- Fiction